Initial Training of Primary School Teachers in the Field of Human Rights in Spain - Neubauer, Adrián (2022)
Objective. This research has, as a general objective, to know how Spanish universities train future teachers of Primary Education in the field of human rights. Method. For this and based on the documentary analysis approach and the software IBM SPSS Statistics 26, we have analyzed 54 teaching guides of 46 Spanish universities that offered the Primary Education Teaching Degree programs during 2018-2019 in Spanish or in another co-official language. Results. The results show that (i) about 65% of Spanish universities have some human rights content in the curricula, (ii) the majority taught in general subjects, (iii) and that the most present competence in the curricula is designing and regulating spaces to promote human rights. Conclusions. From these results, we can infer that these contents have a low presence and relevance in Primary Education Teaching Degree programs in Spain. In addition, the vision conveyed from them is mainly positivist and ignores essential issues such as the best interests of the child and human dignity. In short, it is necessary to rethink the initial training of teachers to enable them to face the great humanitarian challenges of the present and the future.